2015
DOI: 10.1016/j.jviromet.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a multiplex reverse transcription quantitative PCR (RT-qPCR) assay for the rapid detection of Citrus tristeza virus, Citrus psorosis virus, and Citrus leaf blotch virus

Abstract: A single real-time multiplex reverse transcription quantitative polymerase chain reaction (RT-qPCR) assay for the simultaneous detection of Citrus tristeza virus (CTV), Citrus psorosis virus (CPsV), and Citrus leaf blotch virus (CLBV) was developed and validated using three different fluorescently labeled minor groove binding qPCR probes. To increase the detection reliability, coat protein (CP) genes from large number of different isolates of CTV, CPsV and CLBV were sequenced and a multiple sequence alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 99 publications
0
44
0
Order By: Relevance
“…Prior to this study, probe‐based detection methods have been described in other studies, including the multiplex simultaneous detection assay for Citrus viruses (Osman et al . ), for diseases and pathogens of potato tubers (Qu et al . ), for viroids and phytoplasmas of pome fruit trees (Malandraki et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to this study, probe‐based detection methods have been described in other studies, including the multiplex simultaneous detection assay for Citrus viruses (Osman et al . ), for diseases and pathogens of potato tubers (Qu et al . ), for viroids and phytoplasmas of pome fruit trees (Malandraki et al .…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript describes the establishment and application of a reliable and simple multiplex TaqMan RT-qPCR assay for the simultaneous detection of the NYSV and the NMV in narcissus samples. Prior to this study, probe-based detection methods have been described in other studies, including the NYSV 10 À3 10 À8 10 3 10 À8 10 3 NMV 10 À3 10 À8 10 3 10 À8 10 3 multiplex simultaneous detection assay for Citrus viruses (Osman et al 2015), for diseases and pathogens of potato tubers (Qu et al 2011), for viroids and phytoplasmas of pome fruit trees (Malandraki et al 2015), for the Grapevine virus A, B, and D (Osman et al 2013), for the PMTV and for the TRV (Mumford et al 2000). These studies have demonstrated the detection superiority of qPCR over other detection technologies, such as the salient feature of high sensitivity (Fu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete genome sequences of a number of CPsV isolates are available for comparison and a number of molecular tests, hybridisation assays and reverse transcription polymerase chain reaction (RT-PCR) protocols allow a reliable detection of CPsV (Garc ıa et al, 1997;Barthe et al, 1998;Rosa et al, 2007;Osman et al, 2015). A real-time RT-PCR-based assay for simultaneous detection of several citrus viruses, including CPsV, has been developed (Loconsole et al, 2010).…”
Section: Detection and Identification Of The Pestmentioning
confidence: 99%